Tensile Strength Analysis of Resistance Spot Welding - Azi et al., Sirilus Junidin Eoh (TRANSMISI, 2025)
Spot welding is an electrical resistance welding method in which two or more metal sheets are clamped between two electrodes, then a low-voltage electric current is flowed between the electrodes, the metal in contact becomes hot and the temperature rises to the welding temperature, as soon as the welding temperature is reached , the pressure between the electrodes forces the metals together and a welded joint is formed. Tensile testing is to determine the strength of the point weld joint, also to get the stress and strain, in this study using a galvanized mild steel plate with a thickness of 0.2 mm with time variations of 4 seconds, 6 seconds, 8 seconds. The results obtained after a tensile test for 4 seconds obtained a maximum load of 23.5 kg/, and the lowest was 15.7 kg, in 6 seconds the maximum load was 78.8 kg, the lowest was 47.2 kg, in 8 seconds the load was obtained. maximum 87.1 kg, the lowest 43.3 kg. The highest stress from the three times is at 8 seconds at 7.705 kg/mm2, the lowest at 4 seconds is at 1.388 kg/mm2, while the highest strain from the three times is at 8 seconds at 2.434, the lowest is at 4 seconds at 0.034. Keywords: Spot Welding, Time Variation, Tensile Strength